Infusion timing and sleep habits of adults receiving home parenteral and enteral nutrition: A patient‐oriented survey study. Issue 1 (24th September 2022) - Dashti, Hassan S.; Rhyner, Jordan J.; Mogensen, Kris M.; Godbole, Meghna; Saxena, Richa; Compher, Charlene; Winkler, Marion F.
Abstract: Background: The emerging field of chrononutrition investigates the effects of the timing of nutritional intake on human physiology and disease pathology. It remains largely unknown when patients receiving home nutrition support routinely administer home parenteral nutrition (HPN) and/or home enteral nutrition (HEN). Methods: The present descriptive study included data collected from a patient‐oriented survey designed to assess the timing of infusions and sleep habits of patients receiving HPN and HEN in the United States. Results: A total of 100 patients were included. Patients had a mean age of 44.1 years and 81% were female. Among 73 patients supported with HPN and 27 patients supported with HEN, 86% and 44% reported overnight infusions, respectively. The median start and end times of overnight infusions were 2100 (interquartile range [IQR] = 1900–2200) and 0800 (IQR = 0700–1000), respectively, for HPN and 2000 (IQR = 1845–2137) and 0845 (IQR = 0723–1000), respectively, for HEN. Overnight infusions started 2.0 h (IQR = 1.1–3.0) and 2.0 h (IQR = 0.6–3.3) before bedtime for HPN and HEN, respectively, and stopped 12.9 min (IQR = −21.3 to 29.1) and 30.0 min (IQR = −17.1 to 79.3) after wake time for HPN and HEN, respectively. Sleep disruption because of nutrition support or urination was most common among patients receiving infusions overnight compared with those receiving infusions continuously or during the daytime. Conclusions: Our survey study focusing on a novel and medically relevant dimension of nutrition found that most HPN‐dependent and HEN‐dependent patients receive infusions overnight while asleep. Our findings suggest that overnight infusions coinciding with sleep may result in sleep and circadian disruption.